2020
DOI: 10.3390/en13123228
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Design and Analysis of Supersonic Tandem Rotor Blades

Abstract: To explore the flow mechanism and improve the performance of supersonic tandem rotor blades, the supersonic rotor Rotor37 is taken as the prototype and redesigned to an original supersonic tandem rotor. Then, based on the Kriging model, the physical programming method, and improved particle swarm optimization algorithm, a multi-objective optimization methodology is developed and applied to achieve the multi-objective optimization of the supersonic tandem rotor blades. Compared with Rotor37, the mass flow and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The results showed that flutter is realized when the natural frequency of the structure is close to the transient frequency mode of the IGV. Pan et al 12 evaluated the optimal design of a tandem blade under ultrasonic flow for NASA rotor 37 and studied the secondary flow and the resulting shock wave after the blade. Evaluations showed that the use of tandem leads to an increase in mass flow rate and surge margin and a decrease in efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that flutter is realized when the natural frequency of the structure is close to the transient frequency mode of the IGV. Pan et al 12 evaluated the optimal design of a tandem blade under ultrasonic flow for NASA rotor 37 and studied the secondary flow and the resulting shock wave after the blade. Evaluations showed that the use of tandem leads to an increase in mass flow rate and surge margin and a decrease in efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their approach, the design of the experiment, a response surface model, a genetic algorithm, and computational-fluid-dynamics analysis tools were combined together to provide an integrated optimization system. Pan et al [10] developed a multiobjective optimization methodology, which were based on the Kriging model, the physical programming method, and improved particle swarm optimization algorithm, and applied to achieve the multiobjective optimization of the supersonic tandem rotor blades. These methods combine numerical optimization with numerical calculation of flow fields.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization design of modern solenoid valves faces more and more challenges with increasing performance requirements to realize higher latching force, higher output force, and more extensive robustness [1][2][3][4][5][6][7][8][9]. As a means of simulation, the FEM method has the absolute advantage of accuracy, and the disadvantage of efficiency.…”
Section: Introductionmentioning
confidence: 99%